Abundance, length-weight relationships and Fulton’s condition factor of the freshwater cichlid Sarotherodon galilaeus (Pisces: Teleostei: Perciformes) from a sand-dragged man-made lake of Southern Benin, West Africa - GBAGUIDI, Houehanou MAG; ADITE, ALPHONSE (My University, 2016)
Condition factors and growth trends indices such as allometry coefficients are decisive fisheries management tools that evaluate the well-being of fishes, their establishment and the quality of their habitat. We investigated the condition factors and length-weight relationships of a freshwater tilapine cichlid, Sarotherodon galilaeus, that has naturally colonized the artificial lake of Ahozon (South-Benin). S. galilaeus individuals has been sampled every month in the “aquatic vegetation” and in the “open water” habitats with seines, cast nets, gill nets and hooks. This species dominated Lake Ahozon and made about 85.21% of the fish community. Fish sizes showed significant spatial (F 1,5548 =57106.9, p=0.0001) and seasonal (F 2,5547 =82,06, p=0.0001) variations and smaller sizes (18.65
Keywords: Artificial lake; Condition indices; Establishment; Fisheries; Length-weight model.